Nutrient Uptake of Miscanthus in vitro Cultures - Tóth, Szilárd; Pepó, Pál (Acta Agraria Debreceniensis, 2002)
The large biomass production and the low necessary input fertilizer make Miscanthus an interesting, potential non-food crop with broad applications, e.g. for fuel and energy, for thatching, fiber production, for the paper and car industries, as well as for ethanol production.Axillary buds of Miscanthus x giganteus were placed on a shoot inducing nutrient solution (modified Murashige and Skoog, 1962), basic medium supplemented with 0,3 mg l-1 6-Benzylaminopurin. After 40 days of culturing, the axillary buds produced three times more shoots than could normally be harvested. The nutrient content (N, P, K, Ca, Mg) was measured several times during culturing. The results showed that, after 35 days, nitrogen and phosphate were nearly completely taken up. From that time, shoot growth was not observed.After shoot propagation, the plants were transfered into a nutrient solution for root formation (modified Murashige and Skoog, 1962), basic medium supplemented with 0,5 mg l-1 Indole- 3-Butyric acid, and could be potted in soil after about 14 days.